2016
DOI: 10.3126/jpahs.v3i1.20282
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of breech delivery: caesarean section versus vaginal delivery at Patan Hospital, Patan Academy of Health Sciences

Abstract: Introductions:Obstetricians have long debated the role of caesarean section as a potentially safer mode of delivery for the fetus with breech presentation. However, the experience of the health care provider remains a critical element in the decision to pursue a vaginal breech delivery, and it may still be a viable option. The aim of this study is to determine the incidence of breech delivery at Patan Hospital and compare maternal and neonatal outcomes subjected to either vaginal or caesarean section. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
2
3
2
Order By: Relevance
“…Large population based studies are not available to quote the incidence of breech deliveries in our setup. Hospital-based studies conducted in different tertiary level hospitals have reported the breech delivery incidence of 1.9–2.5% [ 11 , 12 ], similar to the incidence reported in our study. But this is slightly lower than the overall incidence of 3–5% [ 1 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Large population based studies are not available to quote the incidence of breech deliveries in our setup. Hospital-based studies conducted in different tertiary level hospitals have reported the breech delivery incidence of 1.9–2.5% [ 11 , 12 ], similar to the incidence reported in our study. But this is slightly lower than the overall incidence of 3–5% [ 1 ].…”
Section: Discussionsupporting
confidence: 90%
“…The higher rates of perinatal morbidity and mortality associated with vaginal breech deliveries in our study are not in compliance with results from other hospitals of Nepal [ 11 13 ]. This may be because of insufficient sample size in study—that those hospitals have lower numbers of total deliveries which allows them to allocate adequate human resources for the management of those cases.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This study was aimed at determining the prevalence and perinatal outcomes of singleton breech delivery at a tertiary level hospital in Nepal. The prevalence of breech presentation in our study was higher than that reported by previous studies conducted in Nepal (1.9-3.1%), 10,13,14 but it was less than the prevalence reported in Ethiopia 5 and Malaysia. 6 Our centre is a tertiary level hospital where significantly large number of cases of high-risk pregnancy including abnormal presentations are referred in, which might be the reason for higher incidence of breech in comparison to previous national studies.…”
Section: Discussioncontrasting
confidence: 85%
“…4 Another study in Patan Academy of Health Sciences concluded that in well-selected cases, the neonatal outcome following assisted vaginal breech delivery and caesarean section may not be different. 5 Adverse perinatal outcome in planned vaginal breech labor at term is associated with fetal growth restriction, oligohydramnios, previous cesarean delivery, gestational diabetes, nulliparity and epidural anesthesia. 6 Women intending vaginal delivery had higher rates of neonatal morbidity (6.0% vs 2.1%), neonatal birth trauma (7.4% vs 0.9%), Apgar <4 at one minute (10.5% vs 1.1%), Apgar <7 at five minutes (4.3% vs 0.5%) and neonatal intensive care unit/special care nursery admissions (16.2% vs 6.6%) than those planning caesarean section.…”
Section: Introductionmentioning
confidence: 99%